Resistencia antibiótica y sobrevida en pacientes con diagnóstico de COVID-19 de la Unidad de Cuidados Intensivos del Hospital III EsSalud Iquitos en el año 2021 - Navarro del Aguila, Ivonne (2025)
Antibiotic resistance represents a challenge in the management of infections in critically ill patients with COVID-19, and may influence the clinical evolution and survival of patients in the Intensive Care Unit of Hospital III EsSalud Iquitos 2021. The objective of the study was to determine the relationship between antibiotic resistance and survival in patients diagnosed with COVID-19 in the Intensive Care Unit of Hospital III EsSalud Iquitos 2021. The observational, analytical, and retrospective quantitative methodology. The results obtained are: 68% were male; average age 56 years; 78% had at least one comorbidity (obesity 54%); 71% of patients reported self-medication with antibiotics and 91% with corticosteroids before admission. 45% had infections by multidrug resistant microorganisms, predominantly Klebsiella pneumoniae and Acinetobacter baumannii. A significant association was found between colistin resistance in bronchial aspirate and reduced survival (p=0.00001); Resistance in blood cultures did not show a statistically significant impact on survival (p>0.005). Age also influenced mortality (p=0.005), confirming that older patients had a shorter survival time. The median hospitalization was 13 days in deceased patients and 14.5 days in survivors, with a median overall survival of 29 days. The Kaplan-Meier analysis showed that survival progressively decreased with hospitalization time and the presence of infections by resistant pathogens. It is concluded that there is a statistically significant relationship between antibiotic resistance and decreased survival in patients with COVID 19 in ICUs. This study highlights the need to optimize antibiotic use protocols, promoting microbiological surveillance strategies and rational administration of antimicrobials to improve clinical outcomes in critically ill patients.